Metabolic syndrome and associated factors among outpatients of Jimma University Teaching Hospital - Abda E (Dove Medical Press, 2016)
Edris Abda,1 Leja Hamza,2 Fasil Tessema,3 Waqtola Cheneke4 1Department of Medicine, College of Medicine and Health Sciences, Madda Walabu University, Bale Robe, 2Department of Internal Medicine, 3Department of Epidemiology, 4Department of Medical Laboratory Sciences and Pathology, College of Health Sciences, Jimma University, Jimma, Ethiopia Background: Developing countries are now experiencing the epidemiologic transition, whereby the burden of chronic diseases, like metabolic syndrome, is increasing. However, no study had previously been conducted to show the status of metabolic syndrome among outpatients of Jimma University Teaching Hospital. Therefore, this study was designed to determine the prevalence of metabolic syndrome and associated factors among adult (≥20 years) patients. Methods: A cross-sectional hospital-based study was conducted in July 2014 among adult (≥20 years) patients attending Jimma University Teaching Hospital, outpatient department. All patients attending the outpatient department and were willing to participate in the study were included. Anthropometric and biochemical measurements were undertaken for all the study subjects to know the status of metabolic syndrome. Metabolic syndrome was identified using the National Cholesterol Education Program’s Adult Treatment Panel III criteria. Results: A total of 225 participants were included in the study, of whom 106 (47.1%) were males and 119 (52.9%) were females. A total of 59 (26%) adults were found to have metabolic syndrome, which was seen more than twice as much in females, 42 (35%), as compared with males, 17 (16%), (P<0.01). The most frequent metabolic syndrome parameters were hypertension (45%), hyperglycemia (39%), decreased high-density lipoprotein (HDL) (31%), central obesity (26%), and elevated triglycerides (18%). Elevated blood pressure is more common in females (44.5%) than in males (34.9%). Decreased HDL-cholesterol was observed among 37% of females versus 24% males (P<0.001) and 6% of males versus 45% females had central obesity (P<0.001). Hypertension and body mass index were significantly lower among males (35% and 14%) than females (45% and 41%) (P<0.01 and P<0.001), respectively. Conclusion: It is demonstrated that metabolic syndrome is prevalent in adult outpatients in Jimma and increases as age increases; it is more common among females than males. Among the five diagnostic criteria for metabolic syndrome, hypertension, hyperglycemia, and low HDL-cholesterol were the most prevalent. As metabolic syndrome is rising at an alarming rate, we recommend that relevant prevention, diagnostics, and therapy in adult outpatients are undertaken. Keywords: metabolic syndrome, Jimma, outpatients, high-density lipoprotein, obesity